2013
DOI: 10.1074/jbc.m113.507384
|View full text |Cite
|
Sign up to set email alerts
|

The RASSF6 Tumor Suppressor Protein Regulates Apoptosis and the Cell Cycle via MDM2 Protein and p53 Protein

Abstract: Background: RASSF6 is a proapoptotic protein related to the Hippo pathway. Results: RASSF6 interacts with MDM2 and stabilizes p53. Conclusion: RASSF6 induces apoptosis and cell cycle arrest via p53. Significance: Our work supports the importance of the C-terminal RASSF-MDM2-p53 axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 28 publications
4
75
0
Order By: Relevance
“…[47][48][49] RASSF6 played as a tumour suppressor gene and suppressed tumour cell growth, invasion and migration and promoted the cell cycle and apoptosis. 48,50 In this study, we demonstrated that RASSF6 expression was downregulated in osteosarcoma tissues and cell lines and downregulated expression of RASSF6 was correlated with advanced TNM stage. Moreover, the expression of RASSF6 was positively correlated with the expression of CASC2 in osteosarcoma tissues.…”
Section: Discussionmentioning
confidence: 85%
“…[47][48][49] RASSF6 played as a tumour suppressor gene and suppressed tumour cell growth, invasion and migration and promoted the cell cycle and apoptosis. 48,50 In this study, we demonstrated that RASSF6 expression was downregulated in osteosarcoma tissues and cell lines and downregulated expression of RASSF6 was correlated with advanced TNM stage. Moreover, the expression of RASSF6 was positively correlated with the expression of CASC2 in osteosarcoma tissues.…”
Section: Discussionmentioning
confidence: 85%
“…RASSF6 association with MST2 inhibits canonical Hippo pathway activation [93]. Interestingly, it was demonstrated that RASSF6 binds to MDM2 and facilitates its self ubiquitination and degradation, stabilizing p53 (like RASSF1A and RASSF3), thereby regulating apoptosis and cell cycle [94]. It also has been demonstrated that, similar to RASSF1A and RASSF2, RASSF6 can inhibit NFjB activity and possibly inflammation by unknown mechanisms [87].…”
Section: Rassf6mentioning
confidence: 99%
“…37,38,46 In the latest published finding, Iwasa showed that RASSF6 regulates apoptosis and the cell cycle via stabilization of p53. 47 Interestingly, in our study, we did not observe any changes in p53 expression related to RASSF6 in ccRCC, and we therefore suspect that RASSF6-induced cell cycle arrest and apoptosis in ccRCC is not dependent on p53 levels.…”
Section: Discussionmentioning
confidence: 59%